Optimization of Polylactic acid and Banana Peel Flour Composition to Enhance the Mechanical Properties and Biodegradability of Eco-Friendly Bioplastics - Abdulloh, Isa Yuanata; Andita Nataria Fitri Ganda; Dewi Puspitasari; Arya Mahendra Sakti (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2025)
This study investigates the development of environmentally friendly bioplastics made from polylactic acid (PLA) reinforced with banana peel flour. Four filler concentrations (0%, 10%, 20%, and 30% wt) were fabricated using injection molding and evaluated through tensile testing (ASTM D638), FTIR spectroscopy, and soil burial biodegradation. Pure PLA showed the highest tensile strength (26.23 MPa) but had the lowest elongation (6.33%) and biodegradation rate (12.8%). Adding 10-20 wt% filler increased stiffness, with the elastic modulus rising from 21.24 MPa to 38.12-26.63 MPa, while maintaining moderate flexibility. The 30 wt% composite demonstrated the most balanced performance, achieving 67.24 MPa tensile strength, 40.12 MPa modulus, 11.49% elongation, and the highest mass loss (20.2%). FTIR results showed a C=O shift from 1743.44 to 1720.46 cm⁻¹ and broad O–H bands, confirming hydrogen bonding and improved interfacial adhesion. Overall, banana peel flour is a promising sustainable filler for PLA-based bioplastics.